Association of the Polymorphism of GSTP1 with the Susceptibility to the Development of Schizophrenia - da Silva Santos, Rodrigo; Anjos, Laura Raniere Borges dos; Silveira, Luciana Carvalho; Borges, Karine Andressa Souza; Reis, Angela Adamski da Silva (Multi-Science Journal, 2018)
Schizophrenia is a complex mental illness characterized by the presence of symptoms such as hallucinations, delusions, catatonic behavior, cognitive impairment among others. Although the studies exceed 100 years, it is one of the mental illnesses less understood. Oxidative stress has been investigated as one of the potential stimulant factors in the development of schizophrenia. For the study of these relationships, the research focuses on polymorphisms of antioxidant enzymes, such as glutathione S-transferase (GST), an important phase II detoxification enzyme. In this context, the aim of the study is to associate the GSTP1 gene polymorphism with the susceptibility to the development of schizophrenia through a case-control study. The knowledge of the genetic predisposition comes as a support for the understanding of schizophrenia, allowing later the establishment of markers of susceptibility to the disease, which when identified will allow the taking of preventive measures and better targeting of the treatment. Methods: For the analysis of the polymorphisms using the PCR-RFLP technique, the samples collected at the Brain Institute Clinic were divided into two groups, case and control, for later study of the heterozygous genotypes (Ile / Val), wild homozygote (Ile / Ile) and mutant homozygote (Val / Val). Results: There was no statistically significant correlation between GSTP1 polymorphism and the risk of developing schizophrenia. Conclusions: In this sense, more studies should be carried out in search of more consistent results, thus allowing a more accurate correlation regarding the role of this polymorphism with the susceptibility to schizophrenia.